Understand and Able to Use Relevant Cost Concepts in Making Decisions that Provide More Provide More Profits Big - Ryanni Sarah Simangungsong; Audira Ginting; Ardi Lumban Tobing; Hamonangan Siallagan (MultiTech Publisher, 2024)
In this era of globalization and an ever-changing economy, companies, especially those operating in the manufacturing industry, must be very careful in managing costs and taking advantage of opportunities to maximize profits. The purpose of this research is important for managers and management teams to continue to learn and adapt, understand industry trends and developments, and make decisions based on accurate and relevant data analysis and information. Qualitative research methods that use in-depth interviews and case studies, especially in the context of the use of relevant costs in decision making. Based on the research results, relevant costs are an important element in the managerial decision making process. It includes costs that will change or arise as a result of a particular decision.